Drying–Rewetting Cycles Affect Nitrate Removal Rates in Woodchip Bioreactors. Issue 1 (1st January 2019) - Maxwell, Bryan M.; Birgand, François; Schipper, Louis A.; Christianson, Laura E.; Tian, Shiying; Helmers, Matthew J.; Williams, David J.; Chescheir, George M.; Youssef, Mohamed A.
Abstract : Woodchip bioreactors are widely used to control nitrogen export from agriculture using denitrification. There is abundant evidence that drying–rewetting (DRW) cycles can promote enhanced metabolic rates in soils. A 287‐d experiment investigated the effects of weekly DRW cycles on nitrate (NO3 ) removal in woodchip columns in the laboratory receiving constant flow of nitrated water. Columns were exposed to continuous saturation (SAT) or to weekly, 8‐h drying‐rewetting (8 h of aerobiosis followed by saturation) cycles (DRW). Nitrate concentrations were measured at the column outlets every 2 h using novel multiplexed sampling methods coupled to spectrophotometric analysis. Drying–rewetting columns showed greater export of total and dissolved organic carbon and increased NO3 removal rates. Nitrate removal rates in DRW columns increased by up to 80%, relative to SAT columns, although DRW removal rates decreased quickly within 3 d after rewetting. Increased NO3 removal in DRW columns continued even after 39 DRW cycles, with ∼33% higher total NO3 mass removed over each weekly DRW cycle. Data collected in this experiment provide strong evidence that DRW cycles can dramatically improve NO3 removal in woodchip bioreactors, with carbon availability being a likely driver of improved efficiency. These results have implications for hydraulic management of woodchip bioreactors and other denitrification practices. Core Ideas: Weekly, 8‐h drying–rewetting (DRW) cycles increased nitrate removal in woodchip columns. Increased nitrate removal in DRW columns declined with number of days since rewetting. Nitrate removal corresponded to greater leaching of dissolved organic C in DRW columns. Effect of DRW was significant even after 39 weekly DRW cycles.